Effects of methylphenidate on mismatch negativity and P3a amplitude of initially psychostimulant-naïve, adult ADHD patients. Issue 3 (5th February 2023) - le Sommer, Julijana; Low, Ann-Marie; Møllegaard Jepsen, Jens Richardt; Fagerlund, Birgitte; Vangkilde, Signe; Habekost, Thomas; Glenthøj, Birte; Oranje, Bob
Abstract: Background: Deficient information processing in ADHD theoretically results in sensory overload and may underlie the symptoms of the disorder. Mismatch negativity (MMN) and P3a amplitude reflect an individual's detection and subsequent change in attention to stimulus change in their environment. Our primary aim was to explore MMN and P3a amplitude in adult ADHD patients and to examine the effects of methylphenidate (MPH) on these measures. Methods: Forty initially psychostimulant-naïve, adult ADHD patients without comorbid ASD and 42 matched healthy controls (HC) were assessed with an MMN paradigm at baseline. Both groups were retested after 6 weeks, in which patients were treated with MPH. Results: Neither significant group differences in MMN nor P3a amplitude were found at baseline. Although 6-week MPH treatment significantly reduced symptomatology and improved daily functioning of the patients, it did not significantly affect MMN amplitude; however, it did significantly reduce P3a amplitude compared to the HC. Furthermore, more severe ADHD symptoms were significantly associated with larger MMN amplitudes in the patients, both at baseline and follow-up. Conclusion: We found no evidence for early information processing deficits in patients with ADHD, as measured with MMN and P3a amplitude. Six-week treatment with MPH decreased P3a but not MMN amplitude, although more severe ADHD-symptoms were associated with larger MMN amplitudes in the patients. Given that P3a amplitude represents an important attentional process and that glutamate has been linked to both ADHD and MMN amplitude, future research should investigate augmenting MPH treatment of less responsive adults with ADHD with glutamatergic antagonists.